PERAN ORANG TUA TERHADAP KEMAJUAN PRESTASI ATLET DI DEDDY TENIS CLUB (DTC) KOTA PONTIANAK - Rokhman, Faisal; Wati, Isti Dwi Puspita; Purnomo, Edi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractTo be able to make athletes who have achievements certainly must be supported by several factors. Several factor thet support a person’s achievement are the supporting facilities and infrastructure, a trainer who is an expert in his field, and the role of parents. One of the mist important factors is parents, because parents have a big contribution to the future of their children. Parents are very helpful in supporting the achievements of children in the field of sports specifically tennis. So the need for research that aims to determine the role parents in supporting the achievements of field tennis athletes. This research is a qualitative research with research results in the form of descriptions. Data sources in this study are trainers, trined children, and parents. Research data obtained through the process of observation with researchers as observers, interviews with general interview types, documentation, and field notes. Data analysis techniques with the process of data reduction. The data obtained will pass the triangulation process in an effort to test the cridibility of the data. The results of the study note that : the majority of parents have not yet played a role in efforts to progress their childern’s achievement. Keywords: The Role Of Parents, Tennis Court.